Structural, content and genre features of regional network media of Belarus: on the example of network media zarya.by and mlyn.by - Belayeva, Inna V. (Journal of the Belarusian State University. Journalism, 2023)
The regional media system of Belarus is undergoing a process of modernisation of the collection, creation, and distribution of information content. A distinctive feature of the modern media space of the country’s regions one can name the development and functioning of such form of mass media as network media. This article defines the main structural, content and genre features of regional network media on the example of the network media zarya.by (Brest region) and mlyn.by (Minsk region).